Assessing metabolic health in a general population: A comparative analysis of three definitions in the Tromsø Study 2015–2016 - Monika Lund Machlik; Sameline Grimsgaard; Laila A. Hopstock; Bjarne K. Jacobsen; Marie W. Lundblad (PLoS ONE, 2025)
Background The concept of metabolically healthy individuals with obesity (MHO) has gained considerable interest. Nevertheless, the lack of a standardized definition for metabolic health complicates the comparison of the prevalence and health implications of MHO. Aim To compare three definitions of metabolic health in terms of their prevalence, overlap, and frequency with which criteria are met within a general population. Methods We used data from 20 581 women and men aged 40–99 years attending the seventh survey of the Tromsø Study (Tromsø7) in 2015–2016. Participants were classified as metabolically healthy (MH) by definitions A) resembling metabolic syndrome (MetS) requiring ≤1/4 MetS components; B) strict requiring fulfillment of 0/4 MetS components, and C) empirically derived definition requiring fulfillment of 0/3 components including diabetes, elevated blood pressure and waist-to-hip ratio. Prevalence of MH was assessed descriptively in categories of normal weight, overweight and obesity based on body mass index (BMI). We used Venn diagrams to present the overlap between the three definitions applied to identify MH individuals, and the frequency of fulfilled components in metabolically unhealthy (MU) individuals (not classified as MH). All analyses were stratified by sex. Results Prevalence of MH was higher in women and participants in lower BMI categories. Using definition A, 50% of women and 38% of men with obesity were classified as MH. Under definition B, 18% of women and 10% of men with obesity were considered MH. Definition C resulted in prevalences of 29% and 18%, in women and men with obesity, respectively. Blood pressure was the most common component in MU individuals, met by 76%−89% of MU women and 81%−93% of MU men, depending on the definition. Conclusion The considerable variation in MH prevalence across different definitions underscores the need for a consensus definition, to further establish public prevention and clinical treatment strategies.